Metaheuristics for Data Clustering and Image Segmentation - Ramadas, Meera; Abraham, Ajith; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this book, differential evolution and its modified variants are applied to the clustering of data and images. Metaheuristics have emerged as potential algorithms for dealing with complex optimization problems, which are otherwise difficult to solve using traditional methods. In this regard, differential evolution is considered to be a highly promising technique for optimization and is being used to solve various real-time problems. The book studies the algorithms in detail, tests them on a range of test images, and carefully analyzes their performance. Accordingly, it offers a valuable reference guide for all researchers, students and practitioners working in the fields of artificial intelligence, optimization and data analytics.
Introduction -- METAHEURISTICS AND DATA CLUSTERING -- REVISED MUTATION STRATEGY FOR DIFFERENTIAL EVOLUTION ALGORITHM -- SEARCH strategy Flower Pollination Algorithm with Differential Evolution. .
Keywords: Computational intelligence; Artificial intelligence; Computer vision; Algorithms; Computational Intelligence; Artificial Intelligence; Computer Vision; Algorithms